Argumentation Skill Assessment for Diagnosing Students' Understanding of Factual, Conceptual, Procedural, and Metacognitive Knowledge: Characteristics of Initial Needs - Walid, A.; Winarni, E. W.; Yanti, F. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to synthesize the characteristics of the initial needs for argumentative skills assessment instruments to diagnose students’ understanding of factual, conceptual, procedural, and metacognitive knowledge. This study used a quasi-experimental method. The technique used was quantitative descriptive research. The research subjects were taken from 50 students who used argumentative patterns in problem-solving on aquatic ecology material so that they were synthesized using argumentation skill indicators. This research was quantitative, with instrument construct design criteria in the cognitive domain based on the taxonomy of science education. The data in the study were collected through several tests to determine argumentation skills. Supporting data were obtained through questionnaires to be analyzed regarding content and learning tools. The data analysis technique calculated the average score of the test questions with criteria according to the skills of argumentation and analysis in terms of content and learning tools. The result of this research is a matrix of rigid test areas with the achievement of indicators of a neatly arranged argumentation skill questionnaire and the results of content analysis and learning tools that support the argumentation instrument.